2016
DOI: 10.1038/srep37638
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the performance of molecularly imprinted polymer nanoparticles for small molecule targets and antibodies in the ELISA format

Abstract: Here we show that molecularly imprinted polymer nanoparticles, prepared in aqueous media by solid phase synthesis with immobilised L-thyroxine, glucosamine, fumonisin B2 or biotin as template, can demonstrate comparable or better performance to commercially produced antibodies in enzyme-linked competitive assays. Imprinted nanoparticles-based assays showed detection limits in the pM range and polymer-coated microplates are stable to storage at room temperature for at least 1 month. No response to analyte was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 32 publications
(50 reference statements)
0
65
0
Order By: Relevance
“…We believe that a way to obtain NPs with a high affinity for application in separation would be to produce NPs using molecular imprinting . Recently, very successful MIP NPs with a sub‐nanomolar affinity were prepared for a range of peptides and proteins using precipitation polymerization, grafting, and solid‐phase imprinting . We intend to test a combination of combinatorial selection of monomers and molecular imprinting in the future for the extension of the present work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that a way to obtain NPs with a high affinity for application in separation would be to produce NPs using molecular imprinting . Recently, very successful MIP NPs with a sub‐nanomolar affinity were prepared for a range of peptides and proteins using precipitation polymerization, grafting, and solid‐phase imprinting . We intend to test a combination of combinatorial selection of monomers and molecular imprinting in the future for the extension of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…The precision of the measurements was evaluated using a coefficient of variation algorithm. Overall, it was found that the synthesized library of NPs showed a modest affinity but lacked specificity, which should be “tuned” by using molecular imprinting to achieve acceptable levels of affinity and obtain specificity required for practical applications …”
Section: Discussionmentioning
confidence: 99%
“…As a result, molecular imprinting has been utilised in a number of applications, including purication and separation, sensing, catalysis, drug delivery, and in a variety of assays and sensors. [1][2][3][4][5][6][7][8][9] A series of signicant breakthroughs in MIP technology came as a result of novel synthetic methods to generate spherical, molecularly imprinted beads as an alternative to conventional MIP particles produced through bulk polymerisation followed by grinding into small particles. 10,11 Nanoparticles in particular offer strong advantages to conventional, bulk MIPs, such as low level of nonspecic binding, quick binding kinetics, and adaptable protocols for replacing antibodies and enzymes in assays and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the MIPs have been used together with surface enhanced Raman spectroscopy, 17 voltammetric sensor 18 and UV-vis spectrometry 19 for detection of histamine, but these methods are not suitable for routine highthroughput screening purpose. Recently, a so called "Pseudo-ELISA" [23][24][25][26] has been developed, where the nanoMIPs were used as replace natural antibodies in ELISA. In the assay, the nano-MIPs were immobilized in a microplate, and the analyte was quantied through the competitive binding between the free analyte and horseradish peroxidase-conjugated analyte.…”
Section: Introductionmentioning
confidence: 99%